Does the Community Reinvestment Act Increase Small Business Lending in Lower Income Neighborhoods? - Mee Jung Kim; Kyung Min Lee; John S. Earle (Institute of Labor Economics (IZA), 2021)
We estimate the impact of the Community Reinvestment Act (CRA) on small business lending in lower-income neighborhoods. Using 2004-2016 panel data on census tracts, we apply a combined regression discontinuity and fixed effect method. We find that the number of small business loans increases by about 3 to 4 percent and the total dollar amount of small business loans by about 6 to 10 percent in tracts becoming treated by the CRA. The results are robust along many dimensions and suggest that the CRA has a positive impact on access to finance for small businesses in lower income areas.
Keywords: G28; G21; R58; 330; financial constraints; small business lending; community reinvestment act; lower income neighborhood